Strengthening the Religious Character of Classroom-Based Students at Sidoarjo State Elementary School - Wulandari, Fitri; Amrullah, Muhlasin (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aims to determine the religious character of class-based students in elementary schools. This research uses a qualitative approach to natural objects. The qualitative approach in this study uses exploratory description to reveal how religious character strengthening is applied in a natural environment, namely in elementary school classrooms. This research data was collected through observation, interview, and documentation. Participants in the study were principals, class teachers, and students, data processing using data collection, data reduction, data presentation, and conclusion. The results showed a strengthening in the religious character of class-based students at SDN. Classroom-based Character Education Strengthening (PPK) is carried out by integrating character values in the learning process thematically or integrated into subjects according to the curriculum.  Classroom-based strengthening of students' religious character at SDN Sidoarjo has created a supportive environment for strengthening students' religious character. This research shows that teachers at Sidoarjo State Elementary School have succeeded in enhancing students' religious character through structured learning in the Learning Implementation Plan (RPP). Religious values have been integrated into daily activities. However, the evaluation of implementing these religious values needs to be improved.